Pengembangan Bahan Ajar Pada Perkuliahan Kalkulus Lanjut Berbasis Pemecahan Masalah - Nurul Hikmah; Muhammad Turmuzi; Nani Kurnati; Ratna Yulis Tyaningsih (FKIP Universitas Mataram, 2026)
Advanced Calculus is a core course in the Mathematics Education Study Program that requires students to demonstrate strong problem solving abilities. Nevertheless, these competencies have not been optimally developed because learning activities are still largely dominated by conventional instructional approaches, with textbooks serving as the primary learning resource. This study aimed to develop and validate problem-solving-based teaching materials for the Advanced Calculus course. This study employed a Research and Development (R&D) approach using the 4D model, which consists of four stages: Define, Design, Develop, and Disseminate. The participants were students enrolled in the Mathematics Education Study Program. The participants were students enrolled in the Mathematics Education Study Program at Mataram University. Data were collected using validation sheets, student response questionnaires, and a problem solving skills test. The results indicated that the developed teaching material met the criteria of validity, practicality, and effectiveness. These results indicate that the problem-solving-based Advanced Calculus teaching material is appropriate for use as one of the learning resources in Advanced Calculus courses and has the potential to enhance students' problem solving skills.